Optimizing Performance of Electric Vehicle Charging Systems Using Solar PV Tree Models - Aris Ansori; Priyo Heru Adiwibowo; Indra Herlamba Siregar; Grummy Wailanduw; Saiful Anwar; Edy Herianto Majlan (Institute of Multidisciplinary Research and Community Service, 2026)
The transition to electric vehicles in the transportation sector has had a positive impact on reducing carbon emissions. However, the availability of electricity from renewable energy sources to charge electric vehicles (EVs) remains very limited in both rural and urban areas. The abundant potential of renewable energy sources, such as solar energy, presents challenges in their application as a power source for charging electric vehicles. This study aims to design and analyze the performance of electric vehicle charging using a solar PV tree model. The solar PV installation uses a 152.4 mm diameter iron pipe, with four solar PVs installed in a circle at 90° intervals and a tilt angle of 15°. Eight solar PV trees are installed in a row on the side of the road in the city of Surabaya, geographically located at latitude south 7°9′-7°21′ and longitude east 112°36′-112°54′. The solar PV tree performance measurement method uses IEC 61724-1. The measured electrical parameters consist of voltage, current, power, and solar PV energy efficiency. Electrical energy measurement is divided into two measurements: electrical energy directly used to charge electric vehicles using a kWh meter, and electrical energy stored in energy storage batteries. Solar PV performance testing uses two types of EV loads: an electric car with a charging capacity of 37.9 kWh and an electric bicycle with a charging capacity of 1.75 kWh. Solar PV testing with a tree model can increase sunlight capture with a leaf-like installation model, and it is easy to place in a park or along the roadside. A solar PV system with a capacity of 8 kWp can produce an average of 18.9718 kWh/day, with an efficiency of 2.63% when the sky is clear and sunlight lasts 8 hours. This solar power plant can charge electric bicycles with 1.22 kWh from a full capacity of 1.75 kWh, and electric cars with 14.31 kWh from a full capacity of 37.9 kWh, with an energy loss of approximately 11.5% during charging. Meanwhile, in terms of economic feasibility, with an electricity price of IDR 2,950/kWh, charging electric vehicles (EVs) is economically feasible with a Benefit Cost Ratio (BCR) of 1.23. The solar power plant's investment capital will be returned in eleven years and two months.Keywords: Solar PV trees, EV charging, Electric vehicles, Renewable energy.